Mid-term follow-up results of neoadjuvant sintilimab combined with chemotherapy for locally advanced resectable esophageal squamous cell carcinoma - Cai, Haibo; Chen, Liji; Huang, Junjun; Ma, Hongmei; Zhang, Shifa; Zhong, Kaize; Yang, Dongbao; Sun, Jiuhe; Liu, Hongfeng; Song, Ru (Frontiers in Immunology, 2024)
BackgroundThe study was conducted in order to investigate whether neoadjuvant immunotherapy combined with chemotherapy can bring survival benefits to patients with locally advanced resectable esophageal squamous cell carcinoma (ESCC) in the real world.MethodsWe retrospectively analysed patients with locally advanced resectable ESCC who underwent surgery at the Jining First People’s Hospital from April 2020 to April 2022. Based on their medical history, the enrolled patients were divided into a neoadjuvant immunochemotherapy plus surgery group (nICT group) and a surgery-only group (S group). Primary endpoints were the two-year overall survival (OS) and disease-free survival (DFS) rates. Secondary endpoints were the safety and efficacy of neoadjuvant immunochemotherapy for patients with locally advanced esophageal cancer, and compared the surgery and postoperative outcomes between the two groups.ResultsA total of 47 patients in the nICT group and 73 patients in the S group were included for further analysis, the stage of the nICT group was more advanced than that of the S group. In the group nICT, 8 patients (17%) achieved the complete pathological response (pCR), 29 patients (61.7%) achieved major pathological response (MPR), including 6 patients (12.8%) with a primary tumor achieving pCR but had residual tumor cells in the lymph nodes (pT0N+), and the treatment-related AES was manageable. The surgery and postoperative outcomes were comparable in both groups. The two-year OS and DFS rates for the nICT group were 91.5% and 85.5% respectively, while those for the S group were 71.2% and 68.5%, and Kaplan–Meier survival analysis and log-rank test revealed significant differences in DFS and OS between the two groups. Patients who achieved MPR in the nICT group showed better DFS and OS, while the Three-cycle subgroup did not exhibit any survival benefit compared to the Two-cycle subgroup.ConclusionsNeoadjuvant sintilimab combined with chemotherapy has promising efficacy and safety in the treatment of locally advanced resectable ESCC. The treatment modality has the potential to become a standard therapy for locally advanced resectable ESCC.